Effect of El Niño/La Niña on tropical easterly jet stream during Asian summer monsoon season. (1st June 2017) - Nithya, K.; Manoj, M. G.; Mohankumar, K.
ABSTRACT: The influence of El Niño/La Niña on the upper‐tropospheric circulation pattern, especially on tropical easterly jet stream (TEJ) over the Asian summer monsoon region, has been studied using ECMWF Reanalysis (ERA) Interim Data for a period of 34 years (1980–2013). The TEJ shows distinctive features during El Niño and La Niña events. The intensity of the TEJ increases and it spreads horizontally and vertically during La Niña years, whereas it weakens and shrinks spatially in El Niño years. Walker circulation over the summer monsoon region shows strong easterlies in La Niña events accompanied with vertically enhanced zonal flow. Lower level (∼850 hPa) convergence as well as upper level (∼150 hPa) divergence is strong in La Niña events and a westward shift of divergence centre is also observed in these years. A strong (weak) anticyclonic flow at upper levels at about 150 hPa is prominent during La Niña (El Niño) years over the Tibetan region causing significant inter‐annual variability of the TEJ. Abstract : Tropical easterly jet (m s −1 ) composites from 15°S to 35°N latitude and 20° and 130°E longitude for (a) El Niño, (b) La Niña and (c) climatology of TEJ from 1980 to 2013 (34 years).